MARKETING MIX FACTORS THAT INFLUENCE THE COMPETITIVENESS OF POLITICAL PARTIES IN GARUT REGENCY, WEST JAVA PROVINCE - Rossy Lambelanova; Hyronimus Rowa; Dedeh Maryani; Triyanto Triyanto (Jurnal Scientia, 2023)
This research is to examine and analyze marketing mix factors that influence the competitiveness of political parties in Garut Regency, West Java Province. The research method used is a mixed method concurrent strategy, where data collection for using qualitative and quantitative methods is carried out at the same time. The research results show that the marketing mix factors of 9 (nine) major parties that will occur in 2023 ahead of the 2024 election in Garut Regency, West Java Province, namely from the 7 (seven) dimensions of the marketing mix variable (X), can be concluded as marketing factors. mix is included in the Fairly Good category. However, the price dimension has a bad category. This is generally because many promises from both legislative members and regional and national leaders have not been fulfilled, for example fuel prices, basic electricity and gas tariffs continue to increase so that people's purchasing power decreases. The condition of political party competitiveness that occurs in Garut Regency, West Java Province from 4 (four) dimensions, namely Arena, Access, Advantage and Activities in the quite good category as well as indicators of Service, segment targets, general strategy, Competitor targets, party channels, diversity party channels, communications, scale, scope and alliances. The influence of marketing mix factors on the competitiveness of political parties in Garut Regency, West Java Province is 50.9%, which means that if the marketing mix variable (X) is increased, it will automatically increase the competitiveness of each political party concerned.